Structuring negotiation and participatory decision making processes for integrated water resources management - URTIGA, Marcella Maia Bezerra de Araújo (2017)
Models are proposed to handle participatory decision processes in watershed committees (WSCs) in Brazil. In summary, the focus is on three different decision problems regarding water management, namely: i) conflicts regarding the use of water, usually regarding water allocation and pollution; ii) prioritizing and choosing alternatives to address a specific watershed problem; iii) and choosing among combinations of alternatives, rather than a single alternative, considering how an individual alternative can complement or substitute another alternative in the same combination of alternatives. Regarding the first decision problem, a WSC has to arbitrate conflicts with respect to the multiple uses of water. The decision makers (DMs) involved in the dispute have to negotiate an agreement. A framework is proposed to assist in identifying issues that can transform a distributive negotiation into an integrative one. This is managed by identifying values that are shared among DMs. Values can be created by using techniques from Value-Focused Thinking to analyze DMs’ value systems and, subsequently, aggregating individual information in a tree of objectives that represents all DMs’ objectives. The framework promotes cooperation and reduces conflicts by having DMs interact with the same purpose, which is to mutually increase the beneficial results of the negotiation. It also assists DMs to visualize an integrative negotiation with different issues of their interest to be negotiated, thus allowing them to think about tradeoff relations. In relation to the second problem, a WSC considers a set of alternatives to solve problems faced by the watershed they represent. For this purpose, this study proposes a model that assists the group decision process by structuring objectives, identifying criteria to evaluate alternatives and identifying alternatives based on the DMs’ objectives. The DMs evaluate the alternatives using an individual value-function. Afterwards, the individual value-functions are aggregated into a group value-function so as to rank the alternatives based on the DMs’ preferences. With this model, the DMs are able to take part in the decision-making process from starting to understand the problem, identifying objectives, creating alternatives, until the process of choosing attributes and selecting alternatives. Thus, the model promotes the DMs’ engagement throughout the whole decision-making process. The third and last decision problem tackled in this study concerns the fact that WSCs faces situations where a solution of a problem is to choose a combination of alternatives instead of choosing a single alternative. In this case, it is important to consider how alternatives together meet the DMs’ objectives. The possible combinations of alternatives are systematically generated using an option form approach. DMs individually rank combinations based on their preferences by providing ordinal information in an interactive way, thus reducing the cognitive burden of making many comparisons or defining tradeoffs. In this approach, each DM expresses his or her preferences using logical preference statements regarding combinations of alternatives by what is called an alternative prioritizing approach. A group recommendation is obtained after aggregating the final individual ranks using the Weighted Voting System by Quartile. A case study for each model is presented to illustrate their applicability.